EFEKTIVITAS MODEL NUMBERED HEADS TOGETHER BERBANTUAN MEDIA BAAMBOOZLE TERHADAP HASIL BELAJAR IPA SISWA KELAS IV - Andita Feby Nurcahyanti; Elly’s Mersina Mursidik; Rissa Prima Kurniawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning outcomes refer to the abilities achieved by students after participating in the learning process, covering cognitive, affective, and psychomotor domains. This study aims to determine the effect of the Cooperative Learning Model of the Numbered Heads Together (NHT) type assisted by Baamboozle media on science learning outcomes of fourth-grade students. This research used a quantitative approach with a True Experimental Design. The subjects were 44 fourth-grade students of SDN 01 Manisrejo, divided into two classes: IV A as the experimental group and IV B as the control group, selected using Simple Random Sampling. The instrument was a multiple-choice test that had been tested for validity, reliability, discrimination index, and difficulty level. Data were analyzed using normality, homogeneity, and hypothesis testing through an independent sample t-test with SPSS 25. The results showed a significant difference between the two classes. The NHT model with Baamboozle effectively improved students’ science learning outcomes.